PUBLIC UNIVERSITY SYSTEM IN NIGERIA: PROBLEMS AND PROSPECTS - Eze, Ifeoma Nonyelum (Multi-Disciplinary Research and Development Journals Int’l, 2025)
Public universities in Nigeria remain the backbone of the national higher education system, serving as critical centers for manpower development, research, innovation, and community service. Since the establishment of University College Ibadan in 1948 as an affiliate of the University of London, the Nigerian university landscape has evolved through successive generations, shaped by government policies, regional aspirations, and socio-economic realities. Despite significant expansion, the system faces persistent challenges, including inadequate funding, infrastructural decay, lecturer shortages, governance weaknesses, corruption, insecurity, and frequent strike actions. These issues undermine the quality and global competitiveness of Nigerian universities. This chapter examines the historical development, conceptual foundations, types, governance structures, and major challenges confronting public universities in Nigeria. It also explores practical solutions, including enhanced funding strategies, academic autonomy, accountability mechanisms, technology integration, leadership reforms, and stronger security frameworks. By linking problems with corresponding remedies, the chapter argues that revitalizing public universities is central to achieving sustainable development and positioning Nigeria as a knowledge-driven economy in Africa and beyond.